Bridging Sacred and Profane Knowledge: The Integration of Diniyah and General Curriculum in Package B Progam at PKBM Cahaya Sunnah - Yenik Wahyuningsih; Achmad Baidowi; Chasan Ma'ruf; Endri Sugati; Fayza Azizah (STAI Ali bin Abi Thalib Surabaya, 2026)
This research aim to analyze curriculum design, breakdown, grouping, and execution of Package B in enhaching the caliber of graduates at PKBM Cileungsi. This research analyze examines the gap between the non-formal education curriculum of Package B and the quality needs of graduates based on religious values at PKBM Cileungsi. It. The research uses a qualitative case study approach at PKBM Cahaya Sunnah Cileungsi, employing interviews, focus group discussions (FGD), and documentation. The data analysis process involves data condensation, data display, and conclusion drawing. To ensure the validity of the findings, source triangulation and member checking are employed. The results show that the Package B curriculum integrates diniyyah (Islamic religious studies) and general education, with a 70 percent emphasis on religious content. The curriculum is designed by the foundation’s internal team through annual work meetings, implemented in a structured manner with subject distribution based on teachers’ competencies, and evaluated periodically every semester. Student achievements include memorization of up to 30 juz, while others achieve around 16 juz, mastery of approximately 90 percent of 42 Hadiths from Arba’in, and academic abilities equivalent to junior high school level, along with significant improvement in religious character. The study concludes that the Package B curriculum model is effective in improving graduate quality through a systematic integration of diniyyah and general education based on religious values. This study is significant because it contributes as a reference for developing PKBM curricula that are religiously based, adaptive, contextual, and capable of enhancing the quality of equivalency education graduates.